MINERALOGICAL CONTROLS ON THE OXYGEN ISOTOPIC COMPOSITIONS OF UOCS - THEIR FORMATION AND IMPLICATIONS FOR THE ORIGIN OF METEORITIC CHONDRULES - Bridges J.C.; Franchi I.A.; Sexton A.S.; Pillinger C.T. (My University, 1999)
We report the results of oxygen isotopic analyses made on mineral separates prepared from chondrules and whole meteorites (UOCs). Feldspar/glass (mainly chondrule mesostasis) is more 16O-poor than the olivine/low Ca pyroxene from which it was separated. This relationship is true both for chondrules and whole meteorites from the three UOC groups. Feldspar and glass have exchanged to a higher degree with 16O-poor gases than ferromagnesian minerals because of the susceptibility of framework silicates and glass to gas-solid diffusion. Olivine and low Ca pyroxene have preserved primitive isotopic compositions. In this way, mineralogy is the dominant control on the oxygen isotopic compositions of UOCs. The similarity of chondrule and whole meteorite isotope compositions suggests that for many UOCs, matrix and chondrules have undergone exchange with the same isotope reservoirs. This exchange postdates chondrule formation and is believed to have occurred after consolidation with the surrounding chondrite matrix in a parent body regolith. After this gas-solid exchange, some isotopic equilibration took place between feldspar and the other relatively 16O-rich solids, as a result of metamorphism. A progressive decrease in the values of δ18Ofeldspar/glass-δ18Oolivine/pyroxene for bulk meteorites occurs with increasing petrologic subtype, from 8000 for a type 3.2 to 2.5% for a type 3.9. A chemical origin for the initial 16O-poor gas reservoirs in the H, L, and LL parent bodies by processes of mass independent fractionation is considered more likely than nucleosynthesis. Feldspar/glass separated from Adrar 003 (L/LL3.2) may be in, or close to having, isotopic equilibrium with the 16O-poor gases for L or LL chondrites. On this basis and assuming that the gas was dominated by H2O and its isotopic composition lay along a line of slope 1 (corresponding to what has been called the equilibrated chondrite line), a tentative upper limit for gas-solid isotopic exchange in UOCs can be calculated, which gives 370°C.